2015
DOI: 10.3389/fnbeh.2015.00127
|View full text |Cite
|
Sign up to set email alerts
|

Both the COMT Val158Met single-nucleotide polymorphism and sex-dependent differences influence response inhibition

Abstract: Reactive and proactive controls of actions are cognitive abilities that allow one to deal with a continuously changing environment by adjusting already programmed actions. They also set forthcoming actions by evaluating the outcome of the previous ones. Earlier studies highlighted sex-related differences in the strategies and in the pattern of brain activation during cognitive tasks involving reactive and proactive control. To further identify sex-dependent characteristics in the cognitive control of actions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…Figure 1a shows the schema of the general task employed, which is a modified version of the reaching countermanding task 21 , 45 , 47 , 65 , 90 , 91 , characterized by the presentation of two types of trials, randomly intermixed: no-signal trials and stop-signal trials (see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1a shows the schema of the general task employed, which is a modified version of the reaching countermanding task 21 , 45 , 47 , 65 , 90 , 91 , characterized by the presentation of two types of trials, randomly intermixed: no-signal trials and stop-signal trials (see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The distributed system for inhibitory control of action must be elaborate and flexible enough to subserve different action contexts, individual differences and genetic variations (Mione et al, 2015). The cerebral cortex contains several types of pyramidal cells in layers II-III and V-VI, and their characteristics depend on the cortical layer, area, and species (van Aerde and Feldmeyer, 2015;Gilman et al, 2017;Luebke, 2017).…”
Section: Inhibition In Motor Controlmentioning
confidence: 99%
“…Because the insight phenomenon, like other complex traits, might be highly polygenic and influenced by thousands of genetic variants with small individual effects (Gratten et al 2014;Manolio et al 2009;Robinson et al 2014), it is important for future studies to validate these results in larger samples. Second, the imbalanced gender ratio in our sample may bias the results of gender-dependent analysis (Mione et al 2015). Although COMT is well known to be sexually dimorphic (Chen et al 2004;Tunbridge et al 2007), gender-dependent effect was not observed in this study.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, since COMT enzyme activity is influenced by gender (Chen et al 2004), many studies have also shown a gender-dependent effect of COMT. For example, Mione et al (2015) and White et al (2014) reported a gender-dependent effect of COMT on inhibitory control and related brain activity. Elton et al (2017) demonstrated that COMT exerted a genderdependent effect on resting brain functional connectivity and brain activity during decisionmaking task.…”
Section: Introductionmentioning
confidence: 99%